Tendencies of development of legal education institutions of higher education - Сопілко, Ірина Миколаївна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
In this article we are talking about specific areas of legal education in higher education establishments, particularly in NAU. Attention is focused on the importance of conduction of lectures with legal practitioners for students, law schools, research and methodological activities where are discussed educational problems and also on the value of effective work of legal consultation "Legal Clinic".